Predictive Analysis of Factors Influencing Depression Status of Nurses in the COVID-19 Pandemic Intensive Care Unit - Li, Jing; Zhang, Yanhua; Li, Li; Yi, Wei; Hao, Yiwei; Bi, Yongjuan (Frontiers in Psychiatry, 2021)
Purpose: Understand the effects of the COVID-19 pandemic on depression in intensive care unit (ICU) nurses, analyze high-risk factors, and propose appropriate measures to maintain physical and mental health. Methods: A total of 78 nurses in ICU of Beijing Ditan Hospital affiliated with Capital Medical University (Beijing area, COVID-19 patient designated hospital) were investigated with self-rating depression scale (SDS). The Cronbach'sαcoefficient was 0.874, the content validity was 0.853, and the internal consistency was good. General information for the questionnaire: gender, marriage, education, age, title, length of service, ICU years of service, COVID-19 pandemic training, concerns about the COVID-19 pandemic, and current health status. Results: According to the SDS scale score, ICU nurses had a total depression score of 51.36 ± 11.667, and the prevalence rate of depression was 44.9% (35/78). Multi-line regression analysis shows that stress perception, work experience in critical diseases, education and other total scores are risk factors for the occurrence of depression. Conclusion: Work experience in critical illness (β = 9.930, P < 0.001) had a positive predictive effect on the total score of depression, while stress perception (β = −0.884, P < 0.001) and education (β = −6.061, P < 0.001) had a negative predictive effect on the total score of depression, and explained 52.7% variation. These findings point to the need for interventions to address psychological distress and provide the necessary support.